Tourism Promotion, Increasing Returns and Domestic Welfare. (25th July 2013) - Shi, Hui; Li, Chuhui
Abstract This paper compares the effect of tourism promotion funded by commodity tax and income tax on domestic welfare in an open economy with increasing returns in the tourism and the non‐tourism sector. A promotion may overcome the under‐production of tourism goods through taking account of the implications of increasing returns, but at the same time, the taxation may have an adverse impact on the rest of the economy. Employing a general equilibrium analysis, we find that the cost of tourism promotion overcomes the benefit, reducing local residents' welfare. Furthermore, commodity tax on tourism consumption is relatively more efficient than income tax in a monopolistic competition, with less adverse impact on the variety of non‐tourism goods. We also clarify the condition for deteriorating 'terms of trade', which only happens when the country has a small allocation of factor endowments.